Peroxisome proliferator-activated receptor-α accelerates α-chlorofatty acid catabolism - Palladino, Elisa N. D. (J Lipid Res, 2017)
α-Chlorofatty aldehydes are generated from myeloperoxidase-derived HOCl targeting plasmalogens, and are subsequently oxidized to α-chlorofatty acids (α-ClFAs). The catabolic pathway for α-ClFA is initiated by ω-oxidation. Here, we examine PPAR-α activation as a mechanism to increase α-ClFA catabolism. Pretreating both HepG2 cells and primary mouse hepatocytes with the PPAR-α agonist, pirinixic acid (Wy 14643), increased the production of α-chlorodicarboxylic acids (α-ClDCAs) in cells treated with exogenous α-ClFA. Additionally, α-ClDCA production in Wy 14643-pretreated wild-type mouse hepatocytes was accompanied by a reduction in cellular free α-ClFA. The dependence of PPAR-α-accelerated α-ClFA catabolism was further demonstrated by both impaired metabolism in mouse PPAR-α(−/−) hepatocytes and decreased clearance of plasma α-ClFA in PPAR-α(−/−) mice. Furthermore, Wy 14643 treatments decreased plasma 2-chlorohexadecanoic acid levels in wild-type mice. Additional studies showed that α-ClFA increases PPAR-α, PPAR-δ, and PPAR-γ activities, as well as mRNA expression of the PPAR-α target genes, CD36, CPT1a, Cyp4a10, and CIDEC. Collectively, these results indicate that PPAR-α accelerates important pathways for the clearance of α-ClFA, and α-ClFA may, in part, accelerate its catabolism by serving as a ligand for PPAR-α.